Aproximações entre Espinosa e Amálio Pinheiro: modos de conhecimento na América Latina - Rayel, Mara Lafourcade (2021)
In this study, as already explained in the title, we performed an approximation between Espinosa’s ideas (17th century), expressed in his Ethics, and Amálio Pinheiro’s theoretical work. Our objective was to establish relationships among the three kinds of knowledge proposed by Espinosa and the baroque mestizo procedures for translation addressed by Amálio Pinheiro in his texts. Based on Pinheiro’s descriptions, we argue that the active affects of joy, which Espinosa described as resulting from the knowledge of the second and third kinds, are already present in the form of cultural production by Latin American people. We bring up to the debate the concept of Espinosa's sign, as a mutilated and confused representation of reality, and Pinheiro’s: magnetized – in the voice of nature and people – and relational: also acting in the dimension of pre-verbal codes. We argue that it is through the increase in the capacity to be simultaneously and multiply affected and, also, the selection of the affects of joy that we can know without the mediation of signs. As it operates underneath the signs, such knowledge modifies the works, so that the contact with them takes place by the apprehension of rhythm and affects rather than by interpretation only. Our hypothesis, therefore, is that the second and third kinds of knowledge proposed by Espinosa, to a relative extent, are already carried out, in this continent, in the mestizo ways of living that use translation and incorporation of multiple pieces of knowledge, practices and feelings, always in harmony with nature, as Pinheiro tells us. The corpus of our work comprises the analysis, comparison, approximation, and sometimes intertwining of the works of the mentioned authors, as well as the selection and analysis of examples of popular music and literature; compositions in which, despite the subjects who produced them, the common notions (second kind of knowledge) and the singular essences (third kind) insist and subsist